Pemikiran Kalam Asy’ariyah - Nunu Burhanuddin; Muhammad Ridwan Efendi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The Asy'ariyah school is one of the schools of kalam science that has been widely studied by academics. The Asy'ariyah sect was founded by Abu Hasan Al-Asy'ari and became one of the forerunners to the birth of the ASWAJA sect or ahlu sunnah waljama'ah. Apart from that, the Asy'ariyah sect has many followers among Muslims in Indonesia. This research aims to analyze the Ash'ariyah sect in historical studies, its influence and main teachings. This research is a type of library research. Data collection techniques come from examining reference sources from relevant research in the form of articles, books and so on. Data analysis techniques by collecting, analyzing and drawing conclusions. The results of the research show that the Ash'ariyah sect became a sect which became the embryo for the birth of the ahl Al-Sunnah Waljama'ah sect which became a para sect from the time of the Prophet Muhammad SAW to his companions. The Ash'ariyah school is a reaction to the Muktazilah school and the main teachings in this school consist of the substance and attributes of God, freedom of will, reason and revelation, goodness and badness and the qadim of the word of Allah SWT, the Being of Allah, justice and the novelty of nature. and the position of the person who sinned.